DEVELOPMENT OF WAR THEORY. AN OVERVIEW - Mehman SULEYMANOV; Ramil SHUKUROV (Journal of Defense Resources Management, 2022)
It is impossible to find a nation in the world that has existed and still exists that has not faced the trials of war in its history and has not tried to emerge from this war with fewer losses and better results. As for the ways to achieve this, after various observations and generalizations, extremely different and dissimilar views and opinions have emerged from time to time. However, since these ideas and considerations could not go beyond the level of social evolution of the time, the issues of interest were explained in a simple way and were based more on subjective thinking. Although the conclusions of the authors of simple ideas, unscientific generalizations and theories are of historical importance, they failed to reveal the objective causes of wars and the regularities of war management. They also created misconceptions about the emergence and operation of wars. This article briefly aims to create a picture of the development of ideas and concepts about the essence and nature of war from ancient times.